An in-shoe ankle supination torque measuring method in running - Fong, D. T. P.; Hong, Y.; Yung, P. S. H.; Fung, K. Y.; Lao, M. L. M.; Chan, K. M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study presented an in-shoe ankle supination torque measuring method in running. One subject performed 56 valid steps during heel-toe walking and running in canvas shoe at different speeds (0.85-4.00m/s). Motion data, ground reaction force data and plantar pressure data were simultaneously recorded. Ankle joint torques in dorsiflexion / plantarflexion and inversion / eversion directions were obtained, and were trimmed from touchdown to takeoff. Pressure values at each of the 99 sensors were used to predict these two parameters by linear stepwise regression. Prediction models with 80%, 85%, 90% and 95% explained variance were constructed. A 9-sensor system is suggested for further development of an in-shoe ankle supination torque measuring device.